Sosialisasi Manfaat Pare (Momordica Charantia) Dalam Meningkatkan Kesehatan Keluarga - Nursaid Nursaid; Mu’ah Mu’ah; Nurul Qomariah; Ibrahim Kamil (Indonesian Journal Publisher, 2024)
Community service is one of PT Muhammadiyah's Catur Dharma which must be carried out by the academic community, especially lecturers at PT. This community service aims to apply the knowledge gained at PT to the community so that it can benefit everyone. Bitter gourd or known by its Latin term, Momordica charantia, is a type of vegetable that tastes bitter. But behind its bitter taste, it turns out that bitter melon has many benefits for the health of the human body. The implementation of this community service is to socialize the benefits of bitter melon for the health of the human body by utilizing vegetables that are found around the community and are very easy to obtain. The socialization of the benefits of bitter melon vegetables was carried out among housewives in Krasak Hamlet, Pancakarya Village, Ajung Jember so that they have knowledge about the importance of consuming bitter melon vegetables for body health. The implementation method for this activity is a lecture method delivered directly by a resource person from MSME Syajarotun Nuqud Bondowoso, an MSME that produces products from bitter melon vegetables. The results of community service with the theme of socializing the benefits of bitter melon for health are 1) the knowledge of housewives about the benefits of bitter melon has increased, 2) the health of housewives and families has improved after knowing the health benefits of bitter melon.